Positive electrode for secondary battery, method for manufacturing the same, and secondary battery

CN117716528BActive Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280051840.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-29
Filing Date
2022-07-26
Publication Date
2026-10-27
Estimated Expiration
2042-07-26

AI Technical Summary

Benefits of technology

[0016]根据本公开,可以抑制电阻增大、并且提高产生电池的内部短路时的安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117716528B_ABST
    Figure CN117716528B_ABST
Patent Text Reader

Abstract

A positive electrode for a secondary battery includes a positive electrode current collector, and a positive electrode active material layer loaded on the positive electrode current collector, the positive electrode active material layer containing active material particles, and an oxide coating film covering at least a portion of a surface of the active material particles, the active material particles including a lithium-containing transition metal oxide, the oxide coating film containing an oxide of a first element other than a nonmetal element, and when a thickness of the positive electrode active material layer is set as TA, a thickness Tb of the oxide coating film at a position of 0.10TA from a surface of the positive electrode current collector of the positive electrode active material layer, and a thickness Tt of the oxide coating film at a position of 0.90TA from the surface of the positive electrode current collector of the positive electrode active material layer satisfy Tb < Tt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure primarily relates to the positive electrode for secondary batteries. Background Technology

[0002] Patent document 1 discloses a lithium-ion battery comprising a positive electrode, a non-aqueous electrolyte, and a negative electrode. The positive electrode includes a conductive material formed of carbon, an alumina deposit dispersed on the surface of the conductive material, and an upper limit potential of 4.5V relative to the redox potential of metallic lithium (vs. Li / Li). + The active material containing lithium oxides is 1 nm or more and 20 nm or less, and the maximum diameter of the aforementioned alumina deposit is 1 nm or more and 20 nm or less.

[0003] Patent Document 2 discloses a positive electrode for a secondary battery, comprising a positive current collector and a positive active material layer containing a positive electrode material disposed on the surface of the positive current collector. The positive electrode material comprises positive active material particles, a first coating film containing an oxide X of a metal element M1 attached to the surface of the positive active material particles, and a second coating film with lithium-ion permeability attached to the surface of the first coating film. The second coating film contains Li. x M2O y The oxide Y shown in (0.5≤x<4, 1≤y<6) is M2, which is at least one selected from the group consisting of B, Al, Si, P, S, Ti, V, Zr, Nb, Ta and La.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-174612

[0007] Patent Document 2: International Publication No. 2019 / 159563 Summary of the Invention

[0008] The problem the invention aims to solve

[0009] In Patent Document 1, by attaching aluminum oxide to the surface of a conductive material formed from carbon material, the decomposition of the non-aqueous electrolyte on the surface of the conductive material is suppressed, thereby improving the capacity of the lithium-ion battery. However, the aluminum oxide deposits scattered on the surface of the conductive material have the disadvantage of increasing the resistance of the positive electrode. In Patent Document 2, the first coating and the second coating may also increase the resistance of the positive electrode.

[0010] On the other hand, the higher the energy density of a secondary battery, the more improvement in safety is required. Among them, it is important to reduce heat generation caused by internal short circuits. If the temperature of the active material particles (positive electrode active material particles) near the short circuit point rises due to heat generation, the resistance of the active material particles tends to decrease sharply.

[0011] Solutions to the Problem

[0012] One aspect of the present disclosure relates to a positive electrode for a secondary battery, which includes a positive electrode current collector and a positive electrode active material layer supported on the aforementioned positive electrode current collector. The aforementioned positive electrode active material layer contains active material particles and an oxide coating covering at least a part of the surface of the aforementioned active material particles. The aforementioned active material particles contain a lithium-containing transition metal oxide. The aforementioned oxide coating contains an oxide of a first element other than non-metallic elements. When the thickness of the aforementioned positive electrode active material layer is defined as TA, the thickness Tb of the aforementioned oxide coating or the presence probability Pb of the aforementioned first element at a position of 0.10TA from the surface of the positive electrode current collector of the aforementioned positive electrode active material layer, and the thickness Tt of the aforementioned oxide coating or the presence probability Pt of the aforementioned first element at a position of 0.90TA from the surface of the positive electrode current collector of the aforementioned positive electrode active material layer satisfy Tb<Tt or Pb<Pt.

[0013] Another aspect of the present disclosure relates to a secondary battery, which includes the above positive electrode for a secondary battery, a negative electrode, a non-aqueous electrolyte, and a separator interposed between the aforementioned positive electrode and the aforementioned negative electrode.

[0014] Still another aspect of the present disclosure relates to a method for manufacturing a positive electrode for a secondary battery, which includes: a step of preparing active material particles containing a lithium-containing transition metal oxide; a step of preparing a positive electrode current collector; and a step of forming a positive electrode active material layer containing the aforementioned active material particles on the surface of the aforementioned positive electrode current collector. The step of forming the aforementioned positive electrode active material layer includes: a supporting step of supporting the aforementioned active material particles on the surface of the aforementioned positive electrode current collector to form a precursor layer; a rolling step of rolling the aforementioned precursor layer; and after the aforementioned rolling step, a coating forming step of exposing the aforementioned active material particles to a gas phase containing a first element other than non-metallic elements, so as to form an oxide coating in a manner covering at least a part of the surface of the aforementioned active material particles. The aforementioned oxide coating contains an oxide of the aforementioned first element. When the thickness of the aforementioned positive electrode active material layer is defined as TA, the thickness Tb of the aforementioned oxide coating or the presence probability Pb of the aforementioned first element at a position of 0.10TA from the surface of the positive electrode current collector of the aforementioned positive electrode active material layer, and the thickness Tt of the aforementioned oxide coating or the presence probability Pt of the aforementioned first element at a position of 0.90TA from the surface of the positive electrode current collector of the aforementioned positive electrode active material layer satisfy Tb<Tt or Pb<Pt.

[0015] The effects of the invention

[0016] According to this disclosure, resistance increase can be suppressed and safety can be improved when an internal short circuit occurs in the battery.

[0017] The novel features of the invention are set forth in the appended claims. The invention relates to both technical features and content, and together with other objects and features of the invention, will be further fully understood by reference to the following detailed description of the accompanying drawings. Attached Figure Description

[0018] Figure 1 A cross-sectional view schematically showing the main part of the positive electrode of one embodiment of the present disclosure.

[0019] Figure 2 To enlarge the representation Figure 1 The diagram shows a cross-sectional view of the main part of the positive electrode.

[0020] Figure 3 This is a three-dimensional schematic diagram showing a portion of a non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure. Detailed Implementation

[0021] The following description provides examples of embodiments of this disclosure, but this disclosure is not limited to these examples. In the following description, specific values ​​and materials are sometimes shown, but other values ​​and materials can be applied as long as the effects of this disclosure are achieved. In this specification, the term "value A to value B" includes both value A and value B and can be understood as "value A or higher and value B or lower." In the following description, when lower and upper limits of values ​​for specific physical properties, conditions, etc., are shown, any combination of any of the shown lower limits and any of the shown upper limits can be used, as long as the lower limit is not higher than the upper limit. When multiple materials are shown, one can be selected for use alone, or two or more can be combined for use.

[0022] Furthermore, this disclosure includes a combination of matters described in any two or more claims selected from the plurality of claims recited in the appended claims. In other words, any combination of matters described in any two or more claims selected from the plurality of claims recited in the appended claims is permissible, provided it does not create a technical contradiction.

[0023] In the following description, the terms "contains" or "includes" are used to express the meanings of "contains (or includes)," "substantially includes," and "includes."

[0024] Secondary batteries include at least non-aqueous electrolyte secondary batteries such as lithium-ion batteries and lithium metal secondary batteries.

[0025] A. Positive electrode for secondary batteries

[0026] The positive electrode for a secondary battery according to the embodiments of the present disclosure includes a positive current collector and a positive active material layer loaded on the positive current collector.

[0027] [Positive current collector]

[0028] The positive current collector is made of a sheet-like conductive material. As a positive current collector, a non-porous conductive substrate (such as metal foil) or a porous conductive substrate (such as mesh, net, or die-cut sheet) can be used.

[0029] [Positive electrode active material layer]

[0030] The positive electrode active material layer is loaded on one or both surfaces of the positive electrode current collector. The positive electrode active material layer is typically a positive electrode compound layer composed of a positive electrode compound, and is in the form of a film or thin film. The positive electrode compound contains active material particles (particles of the positive electrode active material) as an essential component.

[0031] The positive electrode active material layer comprises active material particles and an oxide coating covering at least a portion of the surface of the active material particles. The active material particles contain lithium-containing transition metal oxides. The positive electrode active material layer is formed on the surface of the positive electrode current collector. The positive electrode active material layer may be formed on one or both surfaces of the positive electrode current collector.

[0032] [Oxide Coating]

[0033] An oxide coating covers at least a portion of the surface of the active material particles, which are secondary particles. The oxide coating contains an oxide of a first element other than a non-metallic element. This oxide of the first element has a different crystal structure than the active material particles, or is amorphous. The oxide of the first element other than a non-metallic element may be electrochemically inactive and not exhibit substantial capacity. This oxide coating has the function of suppressing the increase in resistance of the positive electrode and improving safety in the event of an internal short circuit in the battery. If an internal short circuit occurs, the current concentrates, flows near the short circuit point, and generates heat. If the temperature of the active material particles (particles of the positive electrode active material) near the short circuit point rises due to heat generation, there is a tendency for the resistance of the active material particles to decrease sharply. On the other hand, the oxide coating covering at least a portion of the surface of the active material particles functions as a resistive component, preventing a sharp decrease in resistance even if the temperature rises due to heat generation, thus suppressing the increase in short-circuit current.

[0034] Herein, when the thickness of the positive electrode active material layer is defined as TA, a thickness Tb of the oxide coating at a position of 0.10TA from the surface of the positive electrode current collector of the positive electrode active material layer, and a thickness Tt of the oxide coating at a position of 0.90TA from the surface of the positive electrode current collector of the positive electrode active material layer satisfy Tb<Tt. For example, the oxide coating may be formed on the surface of the active material particles to be thicker as it is farther away from the surface of the positive electrode current collector. At this time, the existence probability Pb of the first element at the position of 0.10TA, and the existence probability Pt of the first element at the position of 0.90TA satisfy Pb<Pt.

[0035] By having the above-described distribution of the thickness of the oxide coating, an increase in positive electrode resistance can be suppressed. In the case where the resistance component covering the active material particles close to the surface of the positive electrode current collector is relatively reduced, the current collection performance derived from the active material particles for the positive electrode current collector is not significantly impaired. That is, the oxide coating hardly functions as a resistance component of the positive electrode during normal use of the battery. On the other hand, when an internal short circuit occurs, the resistance of the active material particles in which the resistance of the oxide coating is sharply reduced is supplemented, and an increase in short-circuit current is suppressed.

[0036] The surface of the positive electrode current collector is synonymous with the interface between the positive electrode active material layer and the positive electrode current collector. The position of 0.10TA from the surface of the positive electrode current collector of the positive electrode active material layer is synonymous with the position of 0.10TA from the interface between the positive electrode active material layer and the positive electrode current collector. The position of 0.90TA from the surface of the positive electrode current collector of the positive electrode active material layer is synonymous with the position of 0.90TA from the interface between the positive electrode active material layer and the positive electrode current collector.

[0037] The thickness Tb and the thickness Tt may satisfy 0≤Tb / Tt<1, may satisfy 0.02≤Tb / Tt≤0.7, or may satisfy 0.1≤Tb / Tt≤0.5. Similarly, the existence probabilities Pb and Pt may satisfy 0≤Pb / Pt<1, may satisfy 0.02≤Pb / Pt≤0.8, or may satisfy 0.1≤Pb / Pt≤0.5.

[0038] The thicknesses Tb and Tt of the oxide coating can be measured by cross-sectional observation of the active material particles using SEM or TEM.

[0039] First, the secondary battery is disassembled, and the positive electrode is removed. A cross-section polisher (CP) is used to obtain a cross-section of the positive electrode active material layer. In the cross-sectional image obtained using SEM or TEM, a straight line is drawn from 0.10 TA above the surface of the positive electrode current collector in the positive electrode active material layer. Ten active material particles with a maximum diameter of 5 μm or more are selected from this line. For each particle, the thickness of the oxide coating at one or two intersection points of the above line with the outer edge of the active material particle is measured. The average thickness of these maximum 20 points is calculated. After calculating this average, data that differ from the obtained average by more than 20% are removed, and the average is calculated again. This corrected average is set as the thickness Tb of the oxide coating at the 0.10 TA point. Similarly, the thickness Tt of the oxide coating at the 0.90 TA point is calculated using a straight line drawn from 0.90 TA above the surface of the positive electrode current collector in the positive electrode active material layer.

[0040] The starting point of oxide coating is the interface between the active material particles and the oxide coating. For example, the starting point of oxide coating can be considered as the location where the intensity of the peak of the constituent element of the active material particles, as determined by SEM-EDS analysis, is less than 1 / 10 of the peak of the first element. The ending point of oxide coating can be considered, for example, as the location where the intensity of the peak of the first element, as determined by SEM-EDS analysis, is less than 5% of its maximum value.

[0041] The thickness of the oxide coating can vary from the surface of the positive current collector towards the outer edge. This variation can be continuous or phased, depending on the degree to which it can be understood as a general trend.

[0042] For example, select active material particles at multiple (e.g., 5) different distances from the surface of the positive current collector along a straight line in the thickness direction of the positive electrode active material layer. Measure the thickness of the oxide coating at one or two intersection points of the straight line and the outer edge of the active material particles. Similarly, plot multiple (e.g., 5) straight lines in the thickness direction of the positive electrode active material layer and measure the thickness of the oxide coating. Plot the calculated film thickness on a graph with the horizontal axis representing the distance from the surface of the positive current collector and the vertical axis representing the film thickness. From this graph, if the approximate straight line or curve obtained by the least squares method slopes upwards to the right, it can be determined that, as a whole, the thickness of the oxide coating increases the further outwards from the surface of the positive current collector.

[0043] The thickness Tb of the oxide coating at a position of 0.10 TA from the surface of the positive current collector in the positive electrode active material layer is not particularly limited. From the viewpoint of improving safety during internal short circuits, the thickness Tb can be 0.1 nm or more, 0.5 nm or more, or 1 nm or more. From the viewpoint of suppressing the increase in positive electrode resistance and lithium-ion diffusion, the thickness Tb of the oxide coating can be 50 nm or less, 10 nm or less, or 2 nm or less. For example, the thickness Tb of the oxide coating can be 0.1 nm or more and 50 nm or less, or 0.1 nm or more and 10 nm or less.

[0044] The thickness Tt of the oxide coating at a position of 0.90 TA from the surface of the positive current collector of the positive electrode active material layer is not particularly limited. From the viewpoint of suppressing the increase in positive electrode resistance and lithium-ion diffusion, the thickness Tt can be less than 50 nm, less than 30 nm, less than 10 nm, or less than 2 nm. From the viewpoint of improving safety during internal short circuits, the thickness Tt can be greater than 0.1 nm, greater than 0.5 nm, or greater than 1 nm. For example, the thickness Tt of the oxide coating can be greater than 0.1 nm and less than 50 nm, or greater than 0.1 nm and less than 30 nm.

[0045] The average thickness Ta of the oxide coating is not particularly limited. From the viewpoint of improving safety during internal short circuits, the average thickness Ta of the oxide coating can be 0.1 nm or more, 0.5 nm or more, or 1 nm or more. From the viewpoint of suppressing the increase in cathode resistance and lithium-ion diffusion, the average thickness Ta of the oxide coating can be 50 nm or less, 10 nm or less, or 2 nm or less. For example, the average thickness Ta of the oxide coating is 0.1 nm or more and 50 nm or less.

[0046] The average thickness Ta of the oxide coating can be calculated by averaging the thicknesses Tb and Tt.

[0047] The presence probabilities Pb and Pt can be measured by SEM-EDS analysis or EPMA analysis of the cross-section of the active material particles. The presence probability can be calculated using the spectral intensity ratio of each element at each depth, for example, using the following method. The presence probability Pb ​​can be calculated as the ratio (Rb = Lb / L) of the total length Lb of the portion intersecting with the first element in a straight line drawn at a position of 0.10 TA from the surface of the positive electrode current collector in the positive electrode active material layer, where Lb is 100 μm or more. Similarly, the presence probability Pt can be calculated as the ratio (Rt = Lt / L) of the total length Lt of the portion intersecting with the first element in a straight line drawn at a position of 0.90 TA from the surface of the positive electrode current collector in the positive electrode active material layer, where Lt is 0.90 TA from the surface of the positive electrode current collector in the positive electrode active material layer, where Lt is 0.90 TA from the surface of the first electrode current collector in the positive electrode active material layer. Furthermore, the ratio of the presence probability Pb ​​to Pt: Pb / Pt can be calculated as the ratio of the frequencies at which the first element is detected (the ratio of the detection frequency at the 0.10 TA position to the detection frequency at the 0.90 TA position).

[0048] The positive electrode for measuring thicknesses Tb and Tt, or the probability of existence Pb and Pt, can be taken from a secondary battery with a depth of discharge (DOD) of 90% or more. Depth of discharge (DOD) refers to the ratio of discharged charge to the charge remaining in a fully charged battery. It should be noted that the charge amount when a fully discharged battery (DOD = 100%) is charged to a fully charged state (SOC = 100%, DOD = 0%) (i.e., the full charge amount) is equivalent to the rated capacity. The voltage of a fully charged battery corresponds to the charging termination voltage. The voltage of a fully discharged battery corresponds to the discharging termination voltage.

[0049] The first element is an element other than a nonmetallic element, containing a metallic element, or a so-called half-metallic element. From the viewpoint of maximizing safety improvements, the first element is preferably at least one element selected from the group consisting of elements from Groups 3, 4, 5, and 6 of the periodic table. In particular, the first element is preferably at least one element selected from the group consisting of Al, Ti, Si, Zr, Mg, Nb, Ta, Sn, Ni, and Cr.

[0050] When an oxide coating contains two or more oxides, the oxides can be mixed or configured separately in layers.

[0051] Figure 1 A cross-sectional view schematically showing the main part of the positive electrode of one embodiment of the present disclosure. Figure 2 To further enlarge the representation Figure 1The diagram shows a cross-sectional view of the main part of the positive electrode. The positive electrode 10 includes a positive current collector 11 and a positive active material layer 12. The positive active material layer 12 contains active material particles 20 with an oxide coating. The active material particles 20 with an oxide coating include active material particles 23 and an oxide coating 27 covering at least a portion of their surface.

[0052] Reference Figure 2 Simultaneously, the method for calculating the thickness Tb of the oxide coating 27 covering the active material particles 23 at a position of 0.10TA from the surface of the positive electrode current collector 11 of the positive electrode active material layer 12 will be explained. For convenience, Figure 2 In the diagram, only two active material particles 20 with oxide coatings are shown. The thickness Tt can also be calculated similarly.

[0053] When the thickness of the positive electrode active material layer is set to TA, a straight line is drawn from a position 0.10TA above the surface of the positive electrode current collector of the positive electrode active material layer. Ten active material particles 23 with a maximum diameter of 5 μm or more are selected from this line. For each particle, the thickness of the oxide coating at one or two intersection points (T11, T12, T13, T14, ...) of the above line with the outer edge of the active material particle 23 is measured. The average thickness of these 20 points is calculated. After calculating the average value, data that differ from the obtained average value by more than 20% are removed, and the average value is calculated again. This corrected average value is set as the thickness Tb of the oxide coating at the 0.10TA location.

[0054] B. Secondary battery

[0055] The secondary battery according to the embodiments of this disclosure includes the above-described positive electrode, negative electrode, non-aqueous electrolyte, and a separator sandwiched between the positive electrode and the negative electrode. The secondary battery can be a liquid secondary battery containing an electrolyte as a non-aqueous electrolyte, or an all-solid-state secondary battery containing a solid electrolyte as a non-aqueous electrolyte.

[0056] The following examples illustrate the structure of lithium-ion secondary batteries according to embodiments of this disclosure.

[0057] [positive electrode]

[0058] As the positive electrode, a positive electrode having the characteristics described above is used. The positive electrode active material layer can be constructed using a positive electrode compound. The positive electrode compound must contain active material particles (particles of the positive electrode active material) as an essential component, and can contain binders, thickeners, etc. as optional components.

[0059] The positive electrode active material layer can be a multilayer structure with a first positive electrode additive layer having different morphologies, and one or more other positive electrode additive layers. When the first positive electrode additive layer is closest to the positive electrode current collector, the thickness of the first positive electrode additive layer can be 10 μm or more and 40 μm or less, or 10 μm or more and 30 μm or less. Different morphologies include, for example, different particle sizes of active material particles, different types or compositions of positive electrode active materials, etc. The multilayer structure of the positive electrode active material layer having a first positive electrode additive layer having different morphologies, and one or more other positive electrode additive layers, can be easily identified by observing a cross-section in the thickness direction formed by simultaneously cutting the positive electrode active material layer and the positive electrode current collector.

[0060] The positive electrode active material layer may contain first active material particles having a first average particle size D1 and second active material particles having a second average particle size D2 (D1>D2). In this case, the first positive electrode mixture layer and one or more other positive electrode mixture layers may contain first and second active material particles in different ratios. For example, the first active material particles may comprise 60% or more, or 80% or more, of the active material particles contained in the first positive electrode mixture layer. Similarly, the second active material particles may comprise 60% or more, or 80% or more, of the active material particles contained in one or more other positive electrode mixture layers besides the first positive electrode mixture layer. For example, if the positive electrode active material layer has a two-layer structure with a first positive electrode compound layer on the positive electrode current collector side and a second positive electrode compound layer on top thereon, then at least 80% by mass of the active material particles contained in the first positive electrode compound layer can be the first active material particles, and at least 80% by mass of the active material particles contained in the second positive electrode compound layer can be the second active material particles.

[0061] The first average particle size D1 and the second average particle size D2 can be determined by cross-sections in the thickness direction formed by simultaneously cutting the positive electrode compound layer and the positive electrode current collector. The cross-section can be formed using a cross-section polishing machine (CP). At this time, a thermosetting resin can be filled into the positive electrode compound layer and cured. Then, scanning electron microscope images (hereinafter referred to as SEM images) of the cross-section are taken. SEM images are taken such that at least 10 particles of the first positive electrode active material and at least 10 particles of the second positive electrode active material are observed. Through image processing, the first equivalent circle diameter of the cross-section of the 10 or more particles of the first positive electrode active material is determined, and their average value is taken as D1. Through image processing, the second equivalent circle diameter of the cross-section of the 10 or more particles of the second positive electrode active material is determined, and their average value is taken as D2. Here, the equivalent circle diameter refers to the diameter of a circle with an area equal to the area of ​​the cross-section of the particle (the area of ​​the particle observed in the cross-section of the positive electrode compound layer).

[0062] If the first and second positive electrode active material particles can be separated and recovered by the positive electrode mixture layer, the median particle size (particle size at 50% cumulative volume) of the volume-based particle size distribution of the first and second positive electrode active material particles can be used as D1 and D2. The volume-based particle size distribution can be determined using laser diffraction scattering.

[0063] The positive electrode active material constituting the active material particles includes a lithium-containing transition metal oxide. From the viewpoint of high capacity, it may include a lithium-nickel composite oxide (composite oxide N) containing at least nickel as a transition metal. The proportion of composite oxide N in the positive electrode active material is, for example, 70% by mass or more, or 90% by mass or more, or 95% by mass or more.

[0064] The composite oxide N can be a lithium transition metal oxide containing lithium and Ni, having a layered rock salt-type crystal structure. The proportion of Ni in the lithium transition metal oxide other than Li can be 50 atomic% or more. The lithium transition metal oxide may contain Co; from the viewpoint of low cost and high capacity, the proportion of Co in the lithium transition metal oxide other than Li is preferably 0 atomic% or more and 20 atomic% or less, more preferably 0 atomic% or more and 15 atomic% or less.

[0065] It is generally believed that composite oxides of Ni, in which Ni accounts for more than 50 atomic percent of metal elements other than Li, are prone to crystal structure changes and high resistivity with repeated charging and discharging. In this embodiment, it is assumed that at least a portion of the surface of the active material particles is covered and protected by an oxide coating, thus suppressing this high resistivity.

[0066] The composite oxide N may contain Ni and at least one selected from the group consisting of Co, Mn, and Al. Co, Mn, and Al contribute to the stabilization of the crystal structure of the composite oxide N.

[0067] The percentage of Mn in metallic elements other than Li can be less than 10 atomic% or less than 5 atomic%. The percentage of Mn in metallic elements other than Li can be more than 1 atomic%, more than 3 atomic%, or more than 5 atomic%.

[0068] The percentage of Al in metallic elements other than Li can be less than 10 atomic% or less than 5 atomic%. The percentage of Al in metallic elements other than Li can be more than 1 atomic%, more than 3 atomic%, or more than 5 atomic%.

[0069] Composite oxides N, for example, are represented by the formula: Li α Ni(1-x1-x2-y-z) Co x1 Mn x2 Al y M z O 2+β is represented. The element M is an element other than Li, Ni, Co, Mn, Al and oxygen. α, which represents the atomic ratio of lithium, is, for example, 0.95 ≤ α ≤ 1.05, and increases or decreases during charge and discharge. In (2+β) representing the atomic ratio of oxygen, β satisfies -0.05 ≤ β ≤ 0.05. 1-x1-x2-y-z (=v), which represents the atomic ratio of Ni, is, for example, 0.8 or more, may be 0.85 or more, may be 0.90 or more, or may be 0.95 or more. In addition, v representing the atomic ratio of Ni may be 0.98 or less, and may be 0.95 or less.

[0070] x1, which represents the atomic ratio of Co, is, for example, 0.1 or less (0 ≤ x1 ≤ 0.1), may be 0.08 or less, may be 0.05 or less, or may be 0.01 or less. When x1 is 0, the case where Co is at or below the detection limit is included.

[0071] x2, which represents the atomic ratio of Mn, is, for example, 0.1 or less (0 ≤ x2 ≤ 0.1), may be 0.08 or less, may be 0.05 or less, or may be 0.03 or less. x2 may be 0.01 or more, and may be 0.03 or more.

[0072] y, which represents the atomic ratio of Al, is, for example, 0.1 or less (0 ≤ y ≤ 0.1), may be 0.08 or less, may be 0.05 or less, or may be 0.03 or less. y may be 0.01 or more, and may be 0.03 or more.

[0073] z, which represents the atomic ratio of the element M, is, for example, 0 ≤ z ≤ 0.10, may be 0 < z ≤ 0.05, or may be 0.001 ≤ z ≤ 0.01.

[0074] The element M may be at least one selected from the group consisting of Ti, Zr, Nb, Mo, W, Fe, Zn, B, Si, Mg, Ca, Sr, Sc and Y.

[0075] The composite oxide N is, for example, secondary particles formed by aggregation of a plurality of primary particles. The average particle diameter of the secondary particles of the composite oxide N contained in the entire positive electrode active material is, for example, 3 μm or more and 30 μm or less, and may be 5 μm or more and 25 μm or less.

[0076] The average particle size of secondary particles refers to the particle size that accounts for 50% of the total volume in a particle size distribution determined by laser diffraction scattering (volume average particle size). This particle size is sometimes referred to as D50. For example, the measuring apparatus can be the "LA-750" manufactured by Horiba Corporation.

[0077] When the positive electrode active material layer contains a first active material particle having a first average particle size D1 and a second active material particle having a second average particle size D2 (D1>D2), for example, D1 can be 10 μm or more, or 11 μm or more, or 12 μm or more, or 15 μm or more. Alternatively, D1 can be 30 μm or less, or 25 μm or less. On the other hand, D2 can be less than 10 μm, or 8 μm or less, or 6 μm or less, or 5 μm or less. From the viewpoint of improving charge-discharge cycle characteristics, D2 can be 1 μm or more, or 3 μm or more. The D1 / D2 ratio can be, for example, 2 or more and 6 or less, or 3 or more and 5 or less.

[0078] The adhesive used as the positive electrode may be a resin material. Examples of adhesives include fluoropolymers, polyolefin resins, polyamide resins, polyimide resins, acrylic resins, and vinyl resins. One type of adhesive may be used alone, or in combination of two or more.

[0079] Examples of conductive materials include carbon nanotubes (CNTs), carbon fibers other than CNTs, and conductive particles (such as carbon black and graphite).

[0080] There are no particular limitations on the dispersion medium used in positive electrode slurries, and examples include water, alcohol, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0081] Examples of materials that can be used for the positive current collector include stainless steel, aluminum, aluminum alloy, and titanium. The thickness of the positive current collector is not particularly limited; for example, it can be 1–50 μm or 5–30 μm.

[0082] [negative electrode]

[0083] The negative electrode may have a negative current collector and may contain a negative active material layer. The negative active material layer is loaded on one or both surfaces of the negative current collector.

[0084] The negative electrode active material layer can be a negative electrode compound layer composed of a negative electrode compound. The negative electrode compound layer is in the form of a film or thin film. For the negative electrode compound, particles containing negative electrode active material are an essential component, and binders, conductive agents, thickeners, etc., can be included as optional components. Alternatively, lithium metal foil or lithium alloy foil can be attached to the negative electrode current collector as the negative electrode active material layer.

[0085] The negative electrode mixture layer can be formed, for example, by applying a negative electrode slurry prepared by dispersing a negative electrode mixture containing particles of a negative electrode active material, a binder, and the like in a dispersion medium onto the surface of a negative electrode current collector, followed by drying. The dried coating film may be rolled as needed.

[0086] The negative electrode active material contains a material that electrochemically occludes and releases lithium ions, lithium metal, a lithium alloy, and the like. As the material that electrochemically occludes and releases lithium ions, carbon materials, alloy-based materials, and the like are used. Examples of the carbon material include graphite, easily graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), and the like. Among these, graphite, which has excellent charge-discharge stability and low irreversible capacity, is preferred. Examples of the alloy-based material include alloy-based materials containing at least one metal capable of forming an alloy with lithium, and specific examples include silicon, tin, silicon alloys, tin alloys, silicon compounds, and the like. Silicon oxide, tin oxide, and the like can also be used.

[0087] As the silicon-containing alloy-based material, for example, a lithium ion conductive phase and a composite material in which silicon particles are dispersed in the lithium ion conductive phase can be used. As the lithium ion conductive phase, for example, a silicon oxide phase, a silicate phase, a carbon phase, and the like can be used. The main component (for example, 95 to 100 mass%) of the silicon oxide phase can be silicon dioxide. Among these, a composite material composed of a silicate phase and silicon particles dispersed in the silicate phase is preferred from the viewpoints of high capacity and low irreversible capacity. In addition, as the silicate phase, a lithium silicate phase (lithium-containing silicate phase) with low irreversible capacity and high initial charge-discharge efficiency is preferred.

[0088] The lithium silicate phase may be any oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and may contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase can have the formula: Li 2z SiO 2+z A composition represented by (0<z<2). z preferably satisfies the relationship 0<z<1, and more preferably z=1 / 2. Examples of elements other than Li, Si and O that can be contained in the lithium silicate phase include iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al), and the like.

[0089] The carbon phase can be composed of, for example, amorphous carbon with low crystallinity. The amorphous carbon can be, for example, hard carbon, soft carbon, or other types.

[0090] As the negative current collector, a non-porous conductive substrate (such as metal foil) or a porous conductive substrate (such as a mesh, net, or die-cut sheet) can be used. Examples of materials used as the negative current collector include stainless steel, nickel, nickel alloys, copper, and copper alloys.

[0091] As an adhesive, at least one can be selected from the group consisting of polyacrylic acid, polyacrylates and their derivatives. As a polyacrylate, a Li salt or a Na salt is preferred. Cross-linked lithium polyacrylate is particularly preferred.

[0092] Examples of conductive materials include carbon nanotubes (CNTs), carbon fibers other than CNTs, and conductive particles (such as carbon black and graphite).

[0093] Examples of thickeners include carboxymethyl cellulose (CMC) and its modified forms (which also contain salts such as Na salt), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.); saponifications of polymers containing vinyl acetate units such as polyvinyl alcohol; and polyethers (polyoxyethylene, polyoxyethylene, etc.).

[0094] [Separator]

[0095] A separator is sandwiched between the positive and negative electrodes. The separator has high ion permeability and possesses appropriate mechanical strength and insulation. Examples of separators include microporous films, woven fabrics, and nonwoven fabrics. The separator material can be, for example, polyolefins such as polypropylene and polyethylene. The separator may have a heat-resistant insulating layer on at least one surface layer. The heat-resistant insulating layer may contain inorganic oxide fillers as a main component (e.g., 80% by mass or more) or heat-resistant resin as a main component (e.g., 40% by mass or more). The heat-resistant resin can be polyamide resins such as aromatic polyamides, polyimide resins, or polyamide-imide resins.

[0096] [Non-aqueous electrolytes]

[0097] Non-aqueous electrolytes may contain, for example, a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less. Non-aqueous electrolytes may contain known additives.

[0098] As a non-aqueous solvent, examples include cyclic carbonates, chain carbonates, and cyclic carboxylic esters. Examples of cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). One non-aqueous solvent can be used alone or in combination of two or more.

[0099] Examples of lithium salts include lithium salts containing chloric acid (LiClO4, LiAlCl4, LiB). 10 Cl 10 Lithium salts include those containing fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), those containing fluorinated imides (LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), and lithium halides (LiCl, LiBr, LiI, etc.). Lithium salts can be used alone or in combination of two or more.

[0100] As an example of the structure of a lithium-ion secondary battery, one can exemplify a structure in which the positive and negative electrodes, wound together by a separator, are housed together with a non-aqueous electrolyte within a casing. However, this is not the only possibility; other forms of electrode assemblies can also be used. For example, a stacked electrode assembly, where the positive and negative electrodes are layered together by a separator, can also be used. The shape of the battery is also not limited; for example, it can be cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0101] The following is an example of the lithium-ion secondary battery of the present invention, with reference to... Figure 3 The structure of the square non-aqueous secondary battery is explained at the same time.

[0102] The battery comprises a square-bottomed battery casing 4, and an electrode assembly 1 and an electrolyte (not shown) housed within the battery casing 4. The electrode assembly 1 has a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched between them. The negative electrode current collector is electrically connected to the negative terminal 6 disposed on the sealing plate 5 via a negative electrode lead 3. The negative terminal 6 is insulated by the sealing plate 5 through a resin gasket 7. The positive electrode current collector is electrically connected to the back of the sealing plate 5 via a positive electrode lead 2. That is, the positive electrode is electrically connected to the battery casing 4, which also serves as a positive terminal. The sealing plate 5 is fitted around the opening end of the battery casing 4, and the fitting is laser-welded. A non-aqueous electrolyte injection hole is present in the sealing plate 5, which is blocked by a sealing plug 8 after electrolyte injection.

[0103] <Method for manufacturing the positive electrode>

[0104] The method for manufacturing the positive electrode according to the present disclosure includes: a step of preparing active material particles containing lithium transition metal oxide; a step of preparing a positive electrode current collector; and a step of forming a positive electrode active material layer containing active material particles on the surface of the positive electrode current collector.

[0105] The process for forming a positive electrode active material layer includes: a loading process for loading active material particles onto the surface of a positive electrode current collector to form a precursor layer; a calendering process for calendering the precursor layer; and a coating forming process for exposing the active material particles to a gas phase containing a first element other than a non-metallic element after the calendering process, thereby forming an oxide coating film in a manner that covers at least a portion of the surface of the active material particles.

[0106] (I) Loading process (S1)

[0107] The precursor layer can be formed by coating a positive electrode slurry, which consists of the components of the positive electrode additive dispersed in a dispersion medium, onto the surface of the positive electrode current collector and then drying it. The positive electrode additive, as an essential component, contains active material particles (particles of the positive electrode active material), and as an optional component, it can contain binders, thickeners, etc.

[0108] There are no particular limitations on the dispersion medium, and examples include, for instance, alcohols such as water and ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), or mixtures thereof.

[0109] (II) Rolling process (S2)

[0110] The dried positive electrode slurry coating (i.e., the precursor layer) is calendered. The calendering conditions are not particularly limited. Calendering is preferably carried out until the density of the positive electrode active material in the precursor layer reaches 2.5 g / cm³. 3 Above and 4.0 g / cm 3 The following is the preferred value: 2.9 g / cm³ 3 Above and 3.7g / cm 3 In the following, during calendering, it is preferable to set conditions where the surface portion of the precursor layer is densified. Therefore, in the coating formation process described later, the gas phase containing the first element can have more contact with the active material particles present near the outer surface of the positive electrode active material layer. This facilitates the formation of a thicker oxide coating relative to the active material particles that have detached from the surface of the positive electrode current collector.

[0111] (III) Oxide coating formation process (S3)

[0112] Next, the active material particles loaded on the positive electrode current collector are exposed to a gas phase containing the first element. As a result, an oxide coating containing an oxide of the first element is formed on at least a portion of the surface of the active material particles.

[0113] Examples of vapor phase methods include CVD, ALD, and physical vapor deposition (PVD). ALD is particularly preferred from the viewpoint that oxide coatings can be formed at relatively low temperatures. According to ALD, oxide coatings can be formed in an atmosphere below 200°C.

[0114] In the ALD process, an organometallic compound (precursor) containing element I is used as the raw material for oxide coating. In the ALD process, vaporized precursor (raw material gas) and an oxidant are alternately supplied to a reaction chamber containing the target material. This forms an oxide coating of element I on the surface of the target material.

[0115] In the ALD process, the first element is deposited on the surface of the object in atomic layers due to the self-limiting effect. In the ALD process, the overall thickness of the oxide coating is controlled by the cycle number of one cycle, which is the supply (pulse) of the feed gas → exhaust (purge) of the feed gas → supply (pulse) of the oxidant → exhaust (purge) of the oxidant.

[0116] The precursor is an organometallic compound containing element 1. Various organometallic compounds previously used in the ALD process can be used as precursors.

[0117] Examples of Ti-containing precursors include bis(tert-butylcyclopentadienyl)titanium dichloride (IV)(C 18 H 26 C l2 Ti, tetra(dimethylamino)titanium(IV) ([(CH3)2N]4Ti, TDMAT), tetra(diethylamino)titanium(IV) ([(C2H5)2N]4Ti), tetra(ethylmethylamino)titanium(IV) (Ti[N(C2H5)(CH3)]4), titanium(IV) (diisopropoxy-bis(2,2,6,6-tetramethyl-3,5-heptadecanoic acid (Ti[OCC(CH3)3CHCOC(CH3)3]2(OC3H7)2), titanium tetrachloride (TiCl4), titanium isopropoxide (IV) (Ti[OCH(CH3)2]4), titanium ethoxide (IV) (Ti[O(C2H5)]4). Examples of Al-containing precursors include trimethylaluminum ((CH3)3Al, TMA).

[0118] The feed gas can contain multiple precursors. Different types of precursors can be supplied to the reaction chamber simultaneously or sequentially. Alternatively, the types of precursors contained in the feed gas can be changed in each cycle.

[0119] As the oxidant, the oxidant used in the conventional ALD process can be used. Examples of oxidants include water, oxygen, and ozone. The oxidant can be supplied to the reaction chamber in the form of plasma, with the oxidant as a raw material.

[0120] There are no particular limitations on the conditions for the ALD method. From the viewpoint that it is easier to form a thicker oxide coating on the active material particles near the positive electrode current collector, the temperature of the atmosphere containing the precursor or oxidant can be above 10°C and below 200°C, above 25°C and below 200°C, above 100°C and below 200°C, or above 120°C and below 200°C. From the same viewpoint, the pressure in the reaction chamber during processing can be 1 × 10⁻⁶. -5 Pa or higher and 1×10 5 Below Pa, or 1×10 -4 Pa or higher and 1×10 4 Below Pa.

[0121] The temperature of the atmosphere containing precursors or oxidants in the reaction chamber is above 10°C and below 200°C (e.g., above 120°C and below 200°C), and the pressure in the reaction chamber during processing is 1×10⁻⁶. -5 Pa or higher and 1×10 5 When the pressure is below Pa, the pulse time of the raw material gas can be greater than 0.01 seconds or greater than 0.05 seconds. The pulse time of the raw material gas can be less than 5 seconds or less than 3 seconds.

[0122] After the oxide coating is formed, the positive electrode active material layer can be further calendered. There are no particular limitations on the calendering conditions; they can be appropriately set to form a positive electrode active material layer with a specified thickness or density.

[0123] The present disclosure is described in detail below based on embodiments and comparative examples, but the present disclosure is not limited to the following embodiments.

[0124] Example 1

[0125] [The production of the positive electrode]

[0126] The positive electrode active material constituting the active material particles uses a composite oxide N(LiNi) with a layered rock salt-type crystal structure and containing lithium and Ni. 0.85 Co 0.10 Al 0.05 O2). In addition, an aluminum foil with a thickness of 15 μm is prepared as the positive current collector.

[0127] The median particle size D1 in the particle size distribution of the active material particles, determined by laser diffraction scattering, is 13 μm.

[0128] NMP was added to a positive electrode mixture containing active material particles (D1 = 13 μm), acetylene black, and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2.5:2.5 and the mixture was stirred to prepare a positive electrode slurry.

[0129] (I) Loading process (S1)

[0130] A positive electrode slurry is coated on the surface of an aluminum foil that serves as the positive current collector. The coating is then dried to form a precursor layer of the positive electrode active material layer on both sides of the aluminum foil.

[0131] (II) Rolling process (S2)

[0132] Next, the dried precursor layer is calendered to achieve a positive electrode active material density of 3.65 g / cm³. 3 The thickness of the cathode after calendering is adjusted in this way.

[0133] (III) Oxide coating formation process (S3)

[0134] The stack of the positive current collector and the precursor layer (positive electrode precursor) is contained in a specified reaction chamber, and a portion of the active material particles in the precursor layer is covered by an oxide coating using the ALD method according to the following steps.

[0135] Tetra(dimethylamino)titanium (IV) (TDMAT), a precursor serving as the supply source for element I (Ti), is vaporized and supplied to a reaction chamber containing the positive electrode precursor. The pulse duration is set to 0.1 seconds. The temperature of the precursor-containing atmosphere in the reaction chamber is controlled at 200°C, and the pressure at 260 Pa. After 30 seconds, the surface of the positive electrode precursor is covered with a monolayer of the precursor, and excess precursor is purged using nitrogen gas.

[0136] Next, the oxidant (H2O) is vaporized and supplied to the reaction chamber containing the positive electrode precursor. The pulse time is set to 0.015 seconds. The temperature of the atmosphere containing the oxidant is controlled at 200°C and the pressure at 260 Pa. After 30 seconds, excess oxidant is purged with nitrogen.

[0137] The process of supplying precursors, purging, supplying oxidant, and purging (ALD cycle) is repeated 200 times to form a titanium oxide coating.

[0138] The oxide coating was analyzed using SEM, EDS, and ICP. The oxide coating contains Ti. The thickness Tb of the oxide coating covering the active material particles at a position of 0.10TA from the surface of the positive electrode current collector in the positive electrode active material layer is 6 nm. The thickness Tt of the oxide coating covering the active material particles at a position of 0.90TA from the surface of the positive electrode current collector in the positive electrode active material layer is 30 nm. The average thickness Ta of the oxide coating is 18 nm. The Pb / Pt ≒ Tb / Tt = 0.2 was calculated using EPMA analysis.

[0139] [Making the negative electrode]

[0140] A negative electrode slurry was prepared by adding water to a negative electrode mixture containing graphite, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) as negative electrode active materials in a mass ratio of 96:2:2 and stirring. The negative electrode slurry was then coated onto the surface of a copper foil, which serves as the negative electrode current collector. After drying the coating, it was calendered to form negative electrode active material layers on both sides of the copper foil. The density of the negative electrode active material in the negative electrode active material layers was 1.6 g / cm³. 3 The adjustment is made in this manner. The overall thickness of the negative electrode is 170 μm.

[0141] [Preparation of non-aqueous electrolytes]

[0142] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.

[0143] [Making a Second-hand Battery]

[0144] A tab is installed on each electrode, and the positive and negative electrodes are wound into a spiral shape by a separator with the tabs located at the outermost periphery, thereby creating an electrode assembly. The electrode assembly is inserted into a housing made of aluminum laminated film, vacuum dried at 105°C for 2 hours, electrolyte is injected, and the opening of the housing is sealed to obtain a secondary battery A1.

[0145] Example 2

[0146] In the oxide coating formation step S3, the temperature of the atmosphere containing the precursor and oxidant in the reaction chamber is changed to 180°C. Otherwise, the positive electrode and secondary battery A2 are fabricated in the same manner as in Example 1. The thicknesses Tb, Tt, and Ta of the oxide coating are 12 nm, 30 nm, and 21 nm, respectively.

[0147] Example 3

[0148] In the oxide coating formation step S3, the temperature of the atmosphere containing the precursor and oxidant in the reaction chamber is changed to 150°C. Otherwise, the positive electrode and secondary battery A3 are fabricated in the same manner as in Example 1. The thicknesses Tb, Tt, and Ta of the oxide coating are 18 nm, 30 nm, and 24 nm, respectively.

[0149] Example 4

[0150] In the oxide coating formation step S3, the temperature of the atmosphere containing the precursor and oxidant in the reaction chamber is changed to 120°C. Otherwise, the positive electrode and secondary battery A4 are fabricated in the same manner as in Example 1. The thicknesses Tb, Tt, and Ta of the oxide coating are 24 nm, 30 nm, and 27 nm, respectively.

[0151] Example 5

[0152] In the oxide coating formation step S3, the ALD cycle was repeated 100 times, and the positive electrode and secondary battery A5 were fabricated in the same manner as in Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 3 nm, 15 nm, and 9 nm, respectively.

[0153] Example 6

[0154] In the oxide coating formation step S3, the ALD cycle was repeated 60 times, and the positive electrode and secondary battery A6 were fabricated in the same manner as in Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 2 nm, 10 nm, and 6 nm, respectively.

[0155] Example 7

[0156] In the oxide coating formation step S3, the ALD cycle was repeated 20 times, and the positive electrode and secondary battery A7 were fabricated in the same manner as in Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 1 nm, 5 nm, and 3 nm, respectively.

[0157] Comparative Example 1

[0158] The positive electrode and secondary battery B1 are fabricated in the same manner as in Example 1, except that the order of the calendering process S2 and the oxide coating formation process S3 is changed. The thicknesses Tb, Tt, and Ta of the oxide coating are 30 nm, 30 nm, and 30 nm, respectively.

[0159] Comparative Example 2

[0160] In the oxide coating formation process S3, the ALD cycle was repeated 100 times. Otherwise, the positive electrode and secondary battery B2 were fabricated in the same manner as in Comparative Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 15 nm, 15 nm, and 15 nm, respectively.

[0161] Comparative Example 3

[0162] In the oxide coating formation process S3, the ALD cycle was repeated 60 times. Otherwise, the positive electrode and secondary battery B3 were fabricated in the same manner as in Comparative Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 10 nm, 10 nm, and 10 nm, respectively.

[0163] Comparative Example 4

[0164] In the oxide coating formation step S3, the ALD cycle was repeated 20 times. Otherwise, the positive electrode and secondary battery B4 were fabricated in the same manner as in Comparative Example 1. The thicknesses of the oxide coating, Tb, Tt, and Ta, were 5 nm, 5 nm, and 5 nm, respectively.

[0165] Comparative Example 5

[0166] Without performing the oxide coating formation process S3, the positive electrode and secondary battery B5 are fabricated in the same manner as in Comparative Example 1.

[0167] [evaluate]

[0168] The secondary batteries obtained in the examples and comparative examples were evaluated as follows.

[0169] (1) DC resistance value (DCIR)

[0170] In a 25°C environment, the battery was charged at a constant current of 0.3 It until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05 It. It was then discharged for 100 minutes at a constant current of 0.3 It to achieve a State of Charge (SOC) of 50%.

[0171] A battery with a state of charge (SOC) of 50% was discharged for 10 seconds at currents of 0A, 0.1A, 0.5A, and 1.0A, and the voltage value was measured at each discharge. The relationship between the discharge current and the voltage value after 10 seconds was approximated as a straight line using the least squares method, and the DCIR (initial DCIR) was calculated from the absolute value of the slope at that point. The relative values ​​of the DCIR of battery B5 in Comparative Example 5, set to 100%, are shown in Table 1. A larger relative value indicates a larger resistance.

[0172] (2) Piercing test

[0173] (a) At 25°C, the battery is charged with a constant current of 0.3It until the battery voltage reaches 4.2V, and then charged with a constant voltage until the current reaches 0.05It.

[0174] (b) At 25°C, the tip of a round nail (2.7 mm in diameter) was brought into contact with the center of the charged battery from (a), and the nail was pierced at a speed of 1 mm / s. The piercing was stopped as soon as a voltage drop (Δ50 mV) due to an internal short circuit was detected. The surface temperature of the battery was measured 1 minute after the short circuit.

[0175] [Table 1]

[0176]

[0177] As shown in Table 1, for batteries A1 to A7, the increase in resistance can be suppressed, and the safety when an internal short circuit occurs can be improved. For batteries B1 to B3, the safety when an internal short circuit occurs can be improved, but the increase in resistance is difficult to suppress. For batteries B4 and B5, the increase in resistance is suppressed, but the safety when an internal short circuit occurs is difficult to improve.

[0178] Industrial availability

[0179] The positive electrode for secondary batteries disclosed herein and the secondary batteries containing the same are useful for main power supplies of mobile communication devices, portable electronic instruments, electric vehicles, etc.

[0180] The present invention has been described with respect to the preferred embodiments described herein, but this disclosure should not be interpreted as limiting. Various modifications and alterations will naturally be apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the appended claims should be interpreted as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.

[0181] Explanation of reference numerals in the attached figures

[0182] 1 Electrode assembly

[0183] 2 Positive lead

[0184] 3 Negative lead

[0185] 4. Battery casing

[0186] 5 Sealing board

[0187] 6 Negative extremes

[0188] 7. Padding

[0189] 8 seal

[0190] 10 Positive electrode

[0191] 11 Positive current collector

[0192] 12 Positive electrode active material layer

[0193] 20 Active material particles with oxide coating

[0194] 23 Active substance particles

[0195] 27 Oxide Coating

Claims

1. A positive electrode for a secondary battery, comprising a positive current collector and a positive active material layer loaded on the positive current collector. The positive electrode active material layer contains active material particles and an oxide coating covering at least a portion of the surface of the active material particles. The active material particles contain lithium-containing transition metal oxides. The oxide coating contains an oxide of a first element other than a non-metallic element. When the thickness of the positive electrode active material layer is set to TA, the thickness Tb of the oxide coating at a position of 0.10TA from the surface of the positive electrode current collector of the positive electrode active material layer, or the probability of the presence of the first element Pb, and the thickness Tt of the oxide coating at a position of 0.90TA from the surface of the positive electrode current collector of the positive electrode active material layer, or the probability of the presence of the first element Pt, satisfy 0.2≤Tb / Tt<1 or 0≤Pb / Pt≤0.

8.

2. The positive electrode for a secondary battery according to claim 1, wherein, The first element contains at least one element selected from the group consisting of elements from the third, fourth, fifth, and sixth groups of the periodic table.

3. The positive electrode for a secondary battery according to claim 1 or 2, wherein, The first element contains at least one selected from the group consisting of Al, Ti, Si, Zr, Mg, Nb, Ta, Sn, Ni and Cr.

4. The positive electrode for a secondary battery according to claim 1 or 2, wherein, The average thickness Ta of the oxide coating is greater than 0.1 nm and less than 50 nm.

5. A secondary battery comprising a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode as described in claim 1 or 2.

6. A method for manufacturing a positive electrode for a secondary battery, comprising: A process for preparing active material particles containing lithium transition metal oxides; The process of preparing the positive current collector; and The process of forming a positive electrode active material layer containing the active material particles on the surface of the positive electrode current collector. The process of forming the positive electrode active material layer includes: The loading process of loading the active material particles onto the surface of the positive electrode current collector to form a precursor layer; A calendering process for calendering the precursor layer; and Following the calendering process, the active material particles are exposed to a gas phase containing a first element other than a non-metallic element, thereby forming an oxide coating to cover at least a portion of the surface of the active material particles in a coating formation process. The coating formation process is carried out using the ALD method, which is performed at a temperature between 120°C and 200°C. The oxide coating contains an oxide of the first element. When the thickness of the positive electrode active material layer is set to TA, the thickness Tb of the oxide coating at a position of 0.10TA from the surface of the positive electrode current collector of the positive electrode active material layer, or the probability of the presence of the first element Pb, and the thickness Tt of the oxide coating at a position of 0.90TA from the surface of the positive electrode current collector of the positive electrode active material layer, or the probability of the presence of the first element Pt, satisfy 0.2≤Tb / Tt<1 or 0≤Pb / Pt≤0.8.

Citation Information

Patent Citations

  • Lithium ion battery

    JP2017174612A

  • Secondary battery positive electrode, secondary battery, and method for manufacturing secondary battery positive electrode

    WO2019159563A1

  • Power storage device, and method for manufacturing the same

    JP2017097999A